Florid mesenchymal/stromal proliferation in Krukenberg tumours; A case description illustrating this potential diagnostic pitfall - Nafisat Oyewale, MBBS; Danielle O'Neill, MRCOG; San Soo Hoo, MRCOG; Nabeel Salmons, FRCPath (Elsevier, 2021)
Discrimination between primary ovarian neoplasia and ovarian metastases is important as their management and prognosis are markedly different. We hereby describe the case of a 39 year female who presented with bilateral ovarian masses. Histology of the ovaries predominantly showed a hypercellular and markedly oedematous ovarian stroma with features mimicking a sex-cord stromal tumour. Only with extensive tumour sampling were scant signet ring cells identified, allowing for the diagnosis of bilateral metastatic signet ring adenocarcinoma (Krukenberg tumour) to be made. Our case is used to illustrate and highlight the importance of good morphological assessment, adequate tumour sampling alongside the judicious use of immunohistochemistry and tinctorial staining in the evaluation of an ovarian mass in order to avoid misdiagnosis.